CHALLENGES AND CONSIDERATIONS IN PRE-SCHOOL EDUCATION ABROAD - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Pre-school education is a crucial part of a child’s development, providing a foundation for future learning and growth. While pre-school education can vary greatly depending on the country and culture, there are common themes and practices that can be found across many countries. Pre-school education focuses on developing social, emotional, cognitive, and physical skills in young children through play-based learning activities that are designed to be engaging and fun. In this article, we will explore pre-school education abroad, its benefits, challenges, and considerations, and success stories of children who have thrived in pre-school education abroad.